Constructing a New Regionality: Daphne Marlatt and Writing the West Coast - Michelle Hartley (European Journal of American Studies)
This paper argues for “regionality” as a new term to address the intersection of geographical regions and writing from those regions. The limited applicability of traditionally conceived regionalism to the poetry of the Canadian West Coast demonstrates the need for this new term. The suffix “-ity” stands not for a faith in region or region as totality, but “an instance” or “a degree of” region. These “instances” accrue a processual and multiple version of region. Building on the idea of landscape as repository, this article briefly outlines the importance of institutions (the University of British Columbia’s English Department and Poetry Conference in the early 1960s in particular) and literary archives for this methodology. In order to trace a more fugitive regionality, especially one with transnational aesthetic affiliations, one must be able to locate a writer/work among a constellation of documented influences and documented perspectives. This article then argues that Daphne Marlatt’s work from the 1970s to 2013 offers a particularly compelling example of how theorizing regionality can open up perception of regions and the writing that emerges from them.